When in Rome - Huston, Anjelica; DeVito, Danny; Shepard, Dax, 1975-; Heder, Jon, 1978-; Duhamel, Josh, 1972-; Bell, Kristen, 1980-; Arnett, Will.; Diamond, David, 1965-; Weissman, David; Johnson, Mark Steven, 1964-; Touchstone Pictures; Touchstone Home Entertainment (Firm); et al. (Burbank, Calif. : Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2010)
An ambitious young New Yorker, disillusioned with romance, takes a whirlwind trip to Rome, where she defiantly plucks magic coins from a fountain of love, inexplicably igniting the passion of an odd group of suitors: a sausage magnate, a street magician, an adoring painter, and a self-admiring model. But when a charming reporter pursues her with equal zest, how will she know if his love is the real thing?
Special features: Kerplunk! bloopers from Rome; deleted scenes; "Starstruck" music video by 3OH!3; "Stupid love letter" music video by Friday Night Boys.
Music, Christopher Young ; editors, Andrew Marcus, Ryan Folsey ; director of photography, John Bailey.
Anjelica Huston, Danny Devito, Dax Shepard, Jon Heder, Josh Duhamel, Kristen Bell, Will Arnett.
MPAA rating: PG-13; for some suggestive content.
DVD ; widescreen (2.35:1) presentation ; Dolby digital 5.1 surround.
In English, dubbed French or dubbed Spanish, with optional English subtitles for the deaf and hard-of-hearing, French or Spanish subtitles.
Keywords: Museum curators -- Drama; Man-woman relationships -- Drama; Rome (Italy) -- Drama; New York (N.Y.) -- Drama; Romantic comedy films; Fiction films; Video recordings for the hearing impaired; Feature films; Drama; Comedy films